Metabolites of lactic acid bacteria (Labs) from Malaysian fermented foods and a streptomyces SP. for control of fungal growth and mycotoxin production. - Mohd Danial, Azlina Binti (Cranfield University, 2018)
This study examined metabolites produced by (a) lactic acid bacteria (LABs) from Malaysian fermented foods and (b) from a Streptomyces AS1 strain on the control of human fungal pathogens (Trichophyton rubrum, Aspergillus fumigatus, Candida albicans) and mycotoxigenic spoilage fungi (Aspergillus flavus, Fusarium verticillioides, Penicillium verrucosum, Penicillium nordicum). This was followed by (c) identification of the metabolites, (d) examination of the mechanism of action in relation to inhibition of extracellular hydrolytic enzyme activity, fungal growth, sporulation and mycotoxin production and (e) evaluation of the relationship between efficacy of the extracts on colonisation of nails by T. rubrum, and that of stored wheat grain by the mycotoxigenic species P. verrucosum, to control colonisation and ochratoxin A (OTA) contamination. A total of 66 LAB strains, isolated from Malaysian fermented foods, were screened against these fungal pathogens. Only four LAB strains had good efficacy in controlling germination, growth and sporulation of the dermatophyte T. rubrum in-vitro. The Streptomyces AS1 extracts were effective against all the fungal pathogens tested. More detailed studies with some LAB strains showed that Lactobacillus plantarum strain VS1 alone contributed the highest antifungal activity compared to the other three strains examined, alone or in co-culture. Growth of the dermatophyte T. rubrum was inhibited significantly (p<0.05) by VS1 supernatant when using the optimized culture conditions. The best culture conditions were found to be an inoculum size of 3%, 48 h incubation time, a temperature of 35ᴼC, pH 6.2 and glucose as the main carbon source. A total of six metabolites were found in the LABs, with the two major metabolites L-lactic acid (19.1 mg/g cell dry weight (CDW)) and acetic acid (2.2 mg/g CDW). The MIC, IC₅₀ and MFC were 20 mg/mL, 14 mg/mL and 30 mg/mL, respectively. A comparative study showed that the supernatants gave higher efficacy (p<0.05) than the single compound identified in the supernatants and the major compound responsible for the antifungal activity against T. rubrum was L-lactic acid. The possible mechanism of action was studied by measuring the effect of different concentrations (0, 4 and 15 mg/mL) on the inhibition of hydrolytic activity of four key enzymes produced by T. rubrum. The total and specific activities of alkaline phosphatase, N-acetyl-β-glucosaminidase, keratinase and esterase were decreased when compared to the control after treatment with 15 mg/mL of the supernatant and this paralleled effects on fungal growth. However, the sporulation of the treated T. rubrum was similar (p=0.05) to the control at 15 mg/mL but significantly (p<0.05) higher at 4 mg/mL. Subsequent studies on nail media did not detect any alkaline phosphatase, N-acetyl-β-glucosaminidase and keratinase activity from T. rubrum spores and mycelia after treatments with 25 and 50 mg/mL supernatants. The supernatants at 25 mg/mL were able to completely inhibited spore viability and mycelial growth after 7 and 14 days incubation, respectively. For the Streptomyces AS1 strain, the ethyl acetate extract was very effective at inhibiting spore germination of P. verrucosum when compared to that of A. fumigatus and F. verticillioides. The efficacy was further confirmed in studies on a conducive semi-solid YES medium in Bioscreen C assays. The increment of time to detection (TTD) at OD = 0.1 for P. verrucosum treated with AS1 extract at 0.95 and 0.99 aw was the highest amongst the three fungi. The IC₅₀ at 0.95 and 0.99 aԝ was approximately 0.005 ng/mL and 0.15 µg/mL, respectively and the MIC at both aw levels was >40 µg/mL. In addition, OTA production was totally inhibited at 2.5 µg/mL AS1 extract at both aw levels in in- vitro assays. Ten metabolites were identified and three of these were present in concentrations >10 µg/g CDW. These were identified as valinomycin, cyclo(L-Pro-L- Tyr) and cyclo(L-Pro-L-Val). Comparative studies showed that the AS1 ethyl acetate extract which contained a naturally produced mixture of the various compounds significantly (p<0.05) inhibited growth and OTA production by P. verrucosum than the individual compounds. Temporal studies showed inhibition of the four key hydrolytic enzyme (N-acetyl-β-glucosaminidase, esterase, acid and alkaline phosphatase) activities during growth of P. verrucosum and OTA production by 1.25 µg/mL, at both 0.95 and 0.99 aw. However, the specific activity of N-acetyl-β-glucosaminidase and acid phosphatase were higher than in the control at 0.95 aw. The efficacy of different concentrations of AS1 extract were later examined in stored wheat under different moisture content conditions. The AS1 mixture of metabolites significantly (p<0.05) inhibited populations of P. verrucosum isolated from the treated grain when compared to the controls at 0.90 aw. However, the AS1 extract did not significantly (p>0.05) inhibit populations of the mycotoxigenic species at 0.95 aw. The production of OTA was not significantly (p>0.05) reduced by any of the metabolite mixture naturally produced by the Streptomyces AS1 strain.
Keywords: Bacteria; inhibit; fungal pathogen; human; plant